Konstitusionalitas Proses Pemilihan Kepala Otorita Ibu Kota Nusantara Berdasarkan Undang-Undang Nomor 3 Tahun 2022 tengan Ibu Kota Negara - Subandi, Riskayati (UI Scholars Hub, 2023)
The establishment of the Government of the Special Territory of the Capital of Nusantara (Special Regional Government of IKN) as the location of the new capital of Indonesia has raised controversy, especially as regards its position as the special regional government held by the Nusantara Capital Authority Institution (IKN Authority), as well as the differences in the process for selecting government heads. The research was conducted using a normative jurisprudence method that focuses on the analysis of secondary data to determine the constitutionality of regulations relating to the position and process of election of the head of government in the Capital of Nusantara. Special Regional Government of IKN is distinct from other regional administrations because it has special status at the provincial level. Several countries grant equivalent status to their national capitals, including the United States, Australia, Canada, and the Czech Republic. In the federal government, it aims to authorize intervene in managing the national capital and ensure that the federal government remains neutral in taking of national policies. In contrast to a unitary state, which has just one sovereign and one legislature, which regional governments must also follow the law ot the state. The specialty of the Special Regional Government of IKN managed by the IKN Authority, as well as the mechanism of election of the Head of the Authority through the appointment mechanism established by the President after consulting the House, is deemed to be contrary to the Constitution. This is due to the fact that the current process does not reflect the regional democratization system, which has become the demand for reform, as stated in the Republic of Indonesia's 1945 Constitution. Aside from that, the applicable laws and regulations cannot guarantee accountability in the execution of each process.